A pattern of presentation and management of lip cancer in a tertiary institution in Northwestern Nigeria: A retrospective study - Mujtaba Bala; Adebayo Aremu Ibikunle; Ramat Oyebunmi Braimah; Abdulrazaq Olanrewaju Taiwo; Sufiyanu Umar Yabo; Bashar Muhammad Aliyu; Abdullateef Abdulhakeem; Lukman A Olayemi; Sadeeq Fawa Abubakar; Anas Tsafe Bawa (Wolters Kluwer Medknow Publications, 2023)
Introduction: The lips just like any other part of the body could be affected ny myriads of diseases including infection and neoplasm. Surgical management of lip cancer is often challenging in both reconstructive options and outcomes. Aims: This study aimed to assess the pattern of presentation and management of lip cancer in Usmanu Danfodiyo University Teaching Hospital Sokoto. Materials and Methods: This was a retrospective study of cases of lip cancer managed at the Department of Dental and Maxillofacial Surgery, Usmanu Danfodiyo University Teaching Hospital Sokoto, northern Nigeria, over 9 years. Data collected included patients' demographics, lip involved, treatment given, and the treatment outcomes data were analyzed using IBM SPSS version 25. Results: Of the 47 cases in the study, 31 (66.0%) were male and 16 (34.0%) were female and the majority of them were aged over 50 years. The range was 43-76 years with a mean of ± standard deviation of 55.06 ± 8.9. There were no statistically significant differences in either age or gender. The lower lip was involved in 41 (87.2%), whereas the upper lip was involved in 6 (12.8%) cases. Squamous cell carcinoma (SCC) constituted the majority at 42 (89.4%), which were mostly well differentiated. Of the 6 cases of the lower lip, 4 cases were basal cell carcinoma, 1 case was SCC, and the remaining 1 case was sebaceous carcinoma. A total of 38 (80.9%) patients were surgically treated, and the remaining 9 (19.1%), were referred to the oncology department. Of the various options available in the literature for lip reconstruction after tumor excision, nasolabial flap 17 (44.7%) was the most frequently used in our cases, and the outcome of all the surgeries was found satisfactory. Conclusion: Lip cancer is a relatively common cancer in the orofacial region, and the majority is SCC. All the cases of basal cell carcinoma occur in the upper lip. Several options are available for the reconstruction of the lip defect after resection, with the nasolabial flap being a versatile option.